A rare case: uterine arteriovenous malformation and its management with uterine artery embolization - Bhagat, Snehal; Jinturkar, Anagha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
This case report details the medical journey of a 23-year-old female, Gravida 3, Para 1, Living 1, Abortion 1 (P1L1A1), who was referred to the gynaecology outpatient department (OPD) with complaints of persistent vaginal bleeding and abdominal pain. The patient’s medical history, including previous obstetric events, was carefully reviewed. Diagnostic investigations, including pelvic ultrasound and laboratory tests, were performed to identify the underlying cause of her symptoms. Based on the findings, appropriate medical and/or surgical management was initiated to stabilize the patient and address her condition. The case report also highlights the patient’s follow-up and clinical progress post-treatment, emphasizing the importance of comprehensive care in managing gynaecological complications.